Knowledge-Based Economics: The Role of Management in the Reconciliation of Different Points of View and Solving Long-Lasting Controversies Among Economists - Riccardo VALENTE (Communications of International Proceedings, 2025)
The text underlines first of all the existence of two different points of view concerning knowledge-based economy (KBE) – e.g. the traditional optimistic and deeply-rooted in Neoclassical theory KBE definition as an extraordinary phase of development during which knowledge, human capital and innovation disclosed formerly unheard in human history perspectives, and a more pessimistic KBE definition partially connected with Keynesian and Post-Keynesian theory, stressing its similarities with conditions registered at the start of 20th century and its instability due to higher income inequalities, lower growth and capital accumulation rate. To integrate these conflicting views, then, basing on production planning and operation management practice and theory, arguments concerning the issue of whether capacity utilization may be considered always full or at normally high level – so that growth is supply-driven as per mainstream Neoclassical approach – or considered never full nor normal – as per Keynesian and Post-Keynesian argumentation, so that though flexibility of capacity utilization, growth becomes demand-driven – are discussed, arguing that the second approach seems more appropriate and perfectly in line with data concerning 20th and 21st century main market economies evolution. Finally, basing on Neoclassical capacity full-utilization assumptions rejection and the interpretation of changes historically registered in management since the industrial era end as a firms development strategy reorientation toward more flexible and human-capital-intensive production techniques as to adapt to the unstable environment emerging since 1970’s, an integration of supply-driven Neoclassical endogenous growth theory and Post-Keynesian demand-driven one as well as the reconciliation both aforementioned points of view about KBE is presented.
Keywords: Knowledge-based economy; capacity utilization; Post-Keynesian theory; endogenous growth theory